Dual and Triple Epithelial Coculture Model Systems with Donor-Derived Microbiota and THP-1 Macrophages To Mimic Host-Microbe Interactions in the Human Sinonasal Cavities - Charlotte De Rudder (American Society for Microbiology, 2020)
ABSTRACT The epithelium of the human sinonasal cavities is colonized by a diverse microbial community, modulating epithelial development and immune priming and playing a role in respiratory disease. Here, we present a novel in vitro approach enabling a 3-day coculture of differentiated Calu-3 respiratory epithelial cells with a donor-derived bacterial community, a commensal species (Lactobacillus sakei), or a pathobiont (Staphylococcus aureus). We also assessed how the incorporation of macrophage-like cells could have a steering effect on both epithelial cells and the microbial community. Inoculation of donor-derived microbiota in our experimental setup did not pose cytotoxic stress on the epithelial cell layers, as demonstrated by unaltered cytokine and lactate dehydrogenase release compared to a sterile control. Epithelial integrity of the differentiated Calu-3 cells was maintained as well, with no differences in transepithelial electrical resistance observed between coculture with donor-derived microbiota and a sterile control. Transition of nasal microbiota from in vivo to in vitro conditions maintained phylogenetic richness, and yet a decrease in phylogenetic and phenotypic diversity was noted. Additional inclusion and coculture of THP-1-derived macrophages did not alter phylogenetic diversity, and yet donor-independent shifts toward higher Moraxella and Mycoplasma abundance were observed, while phenotypic diversity was also increased. Our results demonstrate that coculture of differentiated airway epithelial cells with a healthy donor-derived nasal community is a viable strategy to mimic host-microbe interactions in the human upper respiratory tract. Importantly, including an immune component allowed us to study host-microbe interactions in the upper respiratory tract more in depth. IMPORTANCE Despite the relevance of the resident microbiota in sinonasal health and disease and the need for cross talk between immune and epithelial cells in the upper respiratory tract, these parameters have not been combined in a single in vitro model system. We have developed a coculture system of differentiated respiratory epithelium and natural nasal microbiota and incorporated an immune component. As indicated by absence of cytotoxicity and stable cytokine profiles and epithelial integrity, nasal microbiota from human origin appeared to be well tolerated by host cells, while microbial community composition remained representative for that of the human (sino)nasal cavity. Importantly, the introduction of macrophage-like cells enabled us to obtain a differential readout from the epithelial cells dependent on the donor microbial background to which the cells were exposed. We conclude that both model systems offer the means to investigate host-microbe interactions in the upper respiratory tract in a more representative way.